OBSERVANCE OF WHO TEN STEPS TOWARDS SUCCESSFUL BREASTFEEDING; A SURVEY FROM POSTPARTUM MOTHERS - Masood, Sumaira; Rahman, Mahmood ur; Mahmood, Humaira; Faisal, Tayyaba; Maroof, Saira; Qureshi, Azhar Masood (Journal of Ayub Medical College Abbottabad, 2016)
Background: Breastfeeding is a physiological phenomenon, nonetheless, this act is a learned behaviour that requires continuous active support to make it successful. This study determines the frequency of mothers practicing successful breastfeeding according to the WHO ten steps at tertiary care hospital. Methods: A descriptive cross sectional study was conducted in the Obstetrics department of Military Hospital, Rawalpindi over six month duration from July to December 2014. Booked mothers aged 15-49 years, having given birth to healthy, singleton baby were included in the study. Questions were asked after taking written informed consent from the mothers after delivery. Data was entered and analysed on SPSS version 20. Results: Out of 148 mothers, 35 (23.7%) mothers were following successful breastfeeding, i.e., knew 7 or more steps. A total of 100 (67.6%) mothers received support for breastfeeding by healthcare staff during their stay in hospital while 19 (12.8%) mothers started breastfeeding within one hour. About 71% had started formula milk along with breastfeeding. About 127 (85.8%) reported that they fed their children on demand and 144 (97.3%) did not use dummies. Statistically significant difference was observed as housewife mothers gave no top feed (p=0.005) and multiparous mothers started breastfeeding within one hour of delivery (p=0.04). Conclusion: The steps to achieve successful breastfeeding are followed to a small extent among mothers. Delayed initiation of breastfeeding and increasing trend towards use of formula feed was observed. Employed, primiparous mothers are the most sensitive group to be focused during antenatal period.